The Relation of Price, Product Quality And Brand Image To Customer Loyalty In Manufacturing Companies - Anggi Supriyanto; Sutrisna Sutrisna; Georgius Listen (Komunitas Dosen Indonesia, 2021)
The purpose of writing this thesis is to determine the extent to which Price (X1), Product Quality (X2) and Brand Image (X3) can affect Customer Loyalty (Y) of human resources. The author conducted research using multiple linear analysis, correlation coefficient analysis, calculating the coefficient of determination, and testing the hypothesis by looking for the t-count value, then comparing t-count with t-table, and testing the hypothesis by finding the f-count, then comparing f-count with f table. The results of the analysis obtained with the following details: From the results of multiple linear analysis obtained the equation Y = 4.361 + 0.403 X1 + 0.516 X2, and from the results of the price coefficient has a positive and very strong correlation to customer loyalty that is equal to 0.689, Product Quality has a positive and very strong correlation to customer loyalty 0.758. From the results of the coefficient of determination (KD) brand image affects customer loyalty by 47.5%, and the remaining 52.5%, influenced by other factors. Based on the results of hypothesis testing, it is obtained that the t-count for the price is 3.309, the t-count for product quality is 4.463, with a t-table of 1.6722 obtained from the t-table distribution for df = 50 – 2 and the level of significance is 0.05. In other words, Ha is accepted and Ho is rejected, because t count > t table. Based on the hypothesis test for model 1, the f arithmetic result is 43,387, for model 2, the f arithmetic result is 31.664, with f table 1.45 with a significant level of 0.000, the number 0.000 < 0.05, thus Ho is rejected and Ha is accepted, because f count > f table. Based on the results of this study, it can be concluded that there is a relationship between product quality and customer loyalty and so on.